Toward Modernization: Using Strategic Development to Address Deficits in the Juvenile Justice System - David McLeod; Emily Roberts (National Youth Advocacy and Resilience Journal, 2023)
The Juvenile Justice System was established on the premise of rehabilitative action for behaviors that have led youth to the criminal justice system. However, the system has increasingly moved away from this original concept toward a punitive model. The authors present how this movement resulted in the devolution of human rights for the youth involved, a decrease in public safety, and a radical departure from fiscal responsibility related to the theoretical origins of rehabilitation. Studies on topics ranging from costs of correctional centers to trauma experienced by youth in these systems, along with many others, are compared to identify specific areas for renovation. Evidence-based pathways are presented to address these concerns along with pragmatic strategies for utilization of a constructed theory focused on the relationship between diversionary policies, attrition, and growth through the reinvestment of existing resources.